Development of Virtual GeoGebra Classroom Media to Improve Spatial Ability of High School Students through REACT Model - Reka Kirana; Isti Hidayah; Amin Suyitno (Didaktik Matematika, 2025)
. Geometry is one of the mathematical taught from elementary to high level. The importance of studying geometry is due to the many benefits and applications it offers in everyday life, namely in the fields of art, construction, computers, and so on. This research aims to develop virtual learning media to improve spatial abilities, which is one of the prerequisite abilities in studying geometry through the REACT learning model. This research is included in the type of development research with 5 stages, namely ADDIE (Analyze, Design, Development, Implementation, and Evaluate). The analyze stage is collecting data related to constraints and needs in geometric material. The design stage is creating the initial framework for learning media. The development stage is the actualization of the analysis and design stages. The implementation stage is the application of virtual media that has been validated in schools. The evaluation stage is giving tests to students as a basis for reviewing the media being developed. Research data was obtained from validation questionnaires and response questionnaires filled in by teachers, students and professionals in their fields. This development product has been assessed as valid, practical and effective in the learning carried out, producing better experimental class scores compared to control class scores without the provision of virtual Geogebra Classroom media.